Improvement of the Turbine Main Stop Valves with Flow Simulation in Erosion by Solid Particle Impact CFD - Z. Mazur; G. Urquiza; R. Campos (International Journal of Rotating Machinery)
The flow field in a steam turbine main stop valve bypass valve (MSVBV) has been investigated by means of CFD simulations. Because the entire flow to the turbine during start ups is carried by the MSVBV it is subject to serious solid particle erosion problems and requires frequent replacement to avoid the catastrophic damage which can occurred when the MSVBV skirt eroded through causing large pieces of metal to be carried directly into the turbine. For some of the most important geometric parameters of the MSVBV, design recommendation have been made.